Predicting Harbor Porpoise Strandings Based on Near-Shore Sightings Indicates Elevated Temporal Mortality Rates - IJsseldijk, Lonneke L.; Camphuysen, Kees C. J.; Keijl, Guido O.; Troost, Gerard; Aarts, Geert (Frontiers in Marine Science, 2021)
The increase in anthropogenic activities and their potential impact on wildlife requires the establishment of monitoring programs and identification of indicator species. Within marine habitats, marine mammals are often used as ecosystem sentinels, which has led to investigations into their abundance, distribution, and mortality patterns. However, trends in sightings and strandings are rarely analyzed in combination. This is necessary to distinguish elevated stranding rates caused by changes in local abundance from increased mortality as a consequence of other natural, environmental or anthropogenic factors. Therefore, the objective of this study was to assess whether harbor porpoise (Phocoena phocoena) stranding frequency in the southern North Sea can be explained by local population density derived from more than 400 thousand hours of systematic observations along the Dutch coast between 1990 and 2018. Since the late 1990s, both the number of stranded porpoises and the sighting rate increased rapidly up to around the mid-2000s, after which they remained high, but with large inter-annual fluctuations. On an annual basis there was a strong correlation between porpoise strandings and sightings, but with a seasonal mismatch. Highest stranding rates occur in late summer, while highest sighting rates occur in early spring. Despite low sighting rates in late summer, August appears to be the best predictor for the monthly variation in the number of stranded porpoises, which could be explained by post-reproductive dispersal and mortality. Excessive high porpoise stranding numbers after accounting for variations in local density could signpost unusual mortality events (UMEs). The corrected stranding rates show that in the early 1990s, when porpoise sightings were rare, and after 2010, the number of stranded porpoises exceeds the expected number. Especially in the summer of 2011, the number of dead porpoises found ashore was excessively high and this might reflect an UME. These results demonstrate that a comparative interpretation of marine mammal strandings and coastal sightings can be a valuable management and conservation tool that could provide an early warning signal for population change.